Direct vs. Indirect workplace discrimination in Kazakhstan - Ozganova, Botagoz; Říhová, Gabriela; Kronberger, Zdeněk; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
Discrimination can have a negative impact on an individual's mental health, and the issue of workplace discrimination is also a problem in Kazakhstan. This study used a qualitative approach with interviews with 15 participants to evaluate how discrimination impacts the mental health of workers in Kazakhstan. The findings revealed that discrimination had a negative influence on most participants' mental health, contributing to anxiety, despair, stress, and other feelings. These findings emphasize the importance of paying more attention to and acting on discrimination and mental health in Kazakhstan, as well as providing a more refined and comprehensive understanding of the impact of discrimination on mental health. The findings of this study may help to shape policy and practice in Kazakhstan and elsewhere to promote better equality in the workplace.
Vedoucí práce: Gabriela Říhová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses